Introduction to medical imaging : physics, engineering and clinical applications - Smith, Nadine, 1962-2010; Webb, Andrew (Andrew G.) (Cambridge : Cambridge University Press, 2011)
Covering the basics of X-rays, CT, PET, nuclear medicine, ultrasound, and MRI, this textbook provides senior undergraduate and beginning graduate students with a broad introduction to medical imaging. Over 130 end-of-chapter exercises are included, in addition to solved example problems, which enable students to master the theory as well as providing them with the tools needed to solve more difficult problems. The basic theory, instrumentation and state-of-the-art techniques and applications are covered, bringing students immediately up-to-date with recent developments, such as combined computed tomography/positron emission tomography, multi-slice CT, four-dimensional ultrasound, and parallel imaging MR technology. Clinical examples provide practical applications of physics and engineering knowledge to medicine. Finally, helpful references to specialised texts, recent review articles, and relevant scientific journals are provided at the end of each chapter, making this an ideal textbook for a one-semester course in medical imaging.
General image characteristics, data acquisition and image reconstruction -- X-ray planar radiology and computed tomography -- Nuclear medicine: planar scintigraphy, SPECT and PET/CT -- Ultrasound imaging -- Magnetic resonance imaging (MRI).
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Diagnostic imaging; Medical physics